An artificial sperm - next year or never? - Md Isa, Muhammad Lokman; Moore, Harry (Informa Healthcare, 2010)
The idea that a sperm or egg might be formed outside of a gonad is perhaps as bizarre today as human assisted conception and test-tube babies were 30-40 years ago and has received a similar amount of media copy. Here, we review briefly the derivation of mammalian germ cells and sperm cells from embryonic stem cells in vitro, ask whether these methods are viable and could provide therapies in the future, and discuss what constitutes an `artificial' sperm.